Perencanaan Embung Konservasi di Laboratorium Lapnagan Terpadu Fakultas Teknik Universitas Lampung - Hidayat, Taufik; Tugiono, Subuh; Purwadi, Ofik Taupik (Universitas Lampung, 2019)
AbstractThis research intended to conserve water resources and build an integrated field laboratory at the Faculty of Engineering of Lampung University. The small dam planning method consists of hydrological analysis, small dam body planning analysis, soil strength stability analysis of reservoir construction, and analysis of the budget plan in small dam construction..Rainfall data uses Polinela rain station data with one point rainfall analysis method. The calculation results obtained using these methods are, type of reservoir with small dam dimensions, height of 3,75 m with a base elevation of +105,00 and peak elevation of +108,75, reservoir length of 165,613 m and width of the lighthouse as wide as 2,60 m, slope with 1:1,5 embung height with reinforcement of stone pairs. The flood discharge is 0,375 m³/s for the planned rain pattern of 90% in Bandar Lampung area and the planned water storage volume is 4.951,404 m². The planned budget for Conservation Embung at the Integrated Field Laboratory of the Faculty of Engineering, University of Lampung is Rp. 2,817,793,499 (two billion eight hundred seventeen million seven hundred ninety three thousand four hundred ninety nine rupiahs). Abstrak Penelitian ini bertujuan untuk mengkonservasi sumber daya air dan membangun laboratorium lapangan terpadu di Fakultas Teknik Universitas Lampung. Metode perencanaan embung ini terdiri dari analisis hidrologi, analisis perencanaan tubuh embung, analisis stabilitas kekuatan tanah terhadap konstruksi embung, dan rencana anggaran biaya pada konstruksi embung. Data hujan menggunakan data stasiun hujan Polinela dengan metode analisis hujan satu titik (point rainfall). Hasil perhitungan didapatkan dengan menggunakan metode-metode tersebut yaitu, tipe embung urugan dengan dimensi embung, tinggi 3,75 m dengan elevasi dasar +105,00 dan elevasi puncak +108,75, panjang embung sebesar 165,613 m dan lebar mercu selebar 2,60 m, kemiringan terhadap tinggi embung 1:1,5 dengan perkuatan pasangan batu. Debit banjir sebesar 0,375 m³/detik untuk pola hujan rencana 90% daerah Bandar Lampung dan volume tampungan air rencana sebesar 4.951,404 m². Rencana anggaran biaya Embung Konservasi di Laboratorium Lapangan Tepadu Fakultas Teknik Universitas Lampung sebesar Rp. 2.817.793.499,- (dua miliyar delapan ratus tujuh belas juta tujuh ratus sembilan puluh tiga ribu empat ratus sembilan puluh sembilan rupiah).